INFLUENCE OF DIFFERENT CAVITY DISINFECTION SOLUTIONS AND LASER SYSTEMS ON REPAIR BOND STRENGTH OF SILORANE BASED COMPOSITE - Alper Kapdan; Feridun Hürmüzlü (Cumhuriyet University, 2021)
Purpose: Evaluating effects of Nd:YAG-laser, Er:YAG-laser, chlorhexidine and ozonated water application which is used for purpose of antibacterial effects, on repair bond strength of silorane based composite. Materials and Methods: 100 cavities (2 mm deep, 3 mm diameter) prepared in acrylic blocks were filled with silorane composite and subjected thermal cycle and divided into 5 groups (N=20). Group 1:Chlorhexidine; Group 2:Ozonated-water; Group 3:Nd:YAG-laser; Group 4:Er:YAG-laser; Group 5 (control): untreated. Composite repair procedure was implemented with the same silorane based composite. Groups divided into 2 subgroups (n=10). One of the subgroups for each group was subjected second thermal cycle. All of the samples tested by a universal test device. Data were analyzed statistically and significance test of the difference between the two means (Kolmogorov-Simirnov), the variance analysis, and Student-t Test used. Results: No statistical difference was observed among groups after first thermal cycle (p>0,05). After the composite repair, there were no statistically significant difference between groups that were subjected to second thermal cycle (p>0,05). When each group was evaluated in themselves on comparing before and after the thermal cycle after the repair operation; as no statistically significant difference between Ozonated-water, Nd:YAG, Er:YAG and Control groups (p>0,05), a statistically significant decrease was observed only in the Chlorhexidine group after thermal cycle (p<0.05). Conclusion: Ozonated-water, Nd:YAG-laser and Er:YAG-laser applications can be used in the repair of silorane-based composite restorations as an alternative antibacterial application, since the application of chlorhexidine reduces the repair bonding strength.